EVALUATION OF THE IMPLEMENTATION OF PROCUREMENT OF GOODS/SERVICES IN THE EMERGENCY OF CORONA VIRUS DISEASE 2019 (COVID-19) AT SLEMAN HOSPITAL - Any Sofiatun (Academic Hospital Journal, 2021)
Background: Sleman Hospital is a referral hospital for Covid-19 patients. The covid-19 pandemic appeared in the current budget year, the budget for handling COVID-19 is not yet in the 2020 Budget Determination Document (DPA). The duties as Commitment Making Officer (PPK) and procurement officer at Sleman Hospital are additional tasks outside of the main duties and functions. . The implementation of the COVID-19 procurement activities at the Sleman Hospital adjusts the translation of the existing funds as determined through the Director's Decree.Objective: To evaluate the implementation of the procurement of goods/services in an emergency period to fulfill the service needs of COVID-19 patients at the Sleman Hospital.Method ; This study uses a qualitative method. Evaluating the implementation of procurement of goods/services during the COVID-19 emergency period in the period April-December 2020. The research subjects are Commitment Making Officers (PPK), Budget User Authorities (KPA), Procurement Officers, Technical Implementation Officers (PPTK), and Goods Users .Results and Discussion: Sleman Hospital in carrying out goods/services procurement activities during the COVID-19 emergency through 3 stages, namely planning, implementation and completion of work. The implementation of the procurement of goods/services is carried out by the Commitment Making Officer (PPK) and the Procurement Officer. Procurement implementation uses the direct appointment procurement method. direct procurement, e-purchasing through LKPP e-catalog and fast tender/auction. Contract signing is carried out at the stage of execution of work. The use of general procurement procedures is carried out prioritizing the principle of procurement of goods/services in an emergency, namely the speed and accuracy of emergency handling. Goods/services procurement activities that use pure APBD funding sources have good achievements, namely above 70%.Conclusion: The implementation of procurement activities for goods/services at RSUD Sleman is guided by special emergency procurement regulations and general procurement regulations regarding government procurement of goods/services  sourced from pure APBD funds.